2015
DOI: 10.2298/hemind140509061s
|View full text |Cite
|
Sign up to set email alerts
|

Acid leaching of oxide-sulphide copper ore prior the flotation: A way for an increased metal recovery

Abstract: The copper mine Cerovo-East Serbia, as well as the other ore bodies in its vicinity, contains a significant amount of oxide copper minerals in their uper layers (>40%). Processing of such mixed ores by the existing concentration technologies leads to a substantial copper losses (<60%). Reduction of "oxide copper", by acid leaching prior the flotation concentration, can increase the overall copper efficiency up to more than 70% in the single-stage leaching, achieving an efficiency in the flotation concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
0
11
0
4
Order By: Relevance
“…In spite of the L-SX-EW applied on an industrial scale a long time ago, different other approaches in research of reprocessing the flotation tailings, originating from heavy metal sulphide ore processing, have been made during last two decades with the aim of recovering the residual copper as well as associated heavy and precious metals. All the methods are based mainly on chemical-and/or bioleaching and the leach liquor treatment which follows, in rare cases, with re-flotation of the leach residue to concentrate additionally the residual sulphide minerals [8][9][10]12]. Recently, attention has been paid to the electro-kinetic remediation in those cases when sulphide mineral content was small and the content of precious metals was negligible.…”
mentioning
confidence: 99%
“…In spite of the L-SX-EW applied on an industrial scale a long time ago, different other approaches in research of reprocessing the flotation tailings, originating from heavy metal sulphide ore processing, have been made during last two decades with the aim of recovering the residual copper as well as associated heavy and precious metals. All the methods are based mainly on chemical-and/or bioleaching and the leach liquor treatment which follows, in rare cases, with re-flotation of the leach residue to concentrate additionally the residual sulphide minerals [8][9][10]12]. Recently, attention has been paid to the electro-kinetic remediation in those cases when sulphide mineral content was small and the content of precious metals was negligible.…”
mentioning
confidence: 99%
“…Međutim, usled sve strožijih ekoloških standarda i stroge kontrole emisije CO2 i SO2, smanjenja kvaliteta koncentrata, kao i rasta cene energenata, hidrometaluške operacije dobijaju na značaju [8]. Upravo zato, poslednjih godina optimizacija procesa luženja ruda koji sadrže bakar u dvovalentnom stanju predmet su brojnih istraživanja [9,10].…”
Section: Uvodunclassified
“…The acidic effluent enters the process as the stream 2 at the flowrate of 8700 L h -1 , and is neutralized by addition of 1073.31 kg h -1 of flotation tailings into each of the five reactors ( Streams 1,5,8,11 and 14) and 442.00 kg h -1 into the sixth reactor (Stream 17) to achieve the pH value of 2 in the output solution (Stream 18). Solid and liquid phases are separated in phase separator after each reactor and solid residues exit the process as output Streams 4,7,10,13,16 and 19. After the phase separation, the obtained solutions are transferred to the next reactor.…”
Section: Computer Simulation Of Neutralisation Of the Acidic Efflumentioning
confidence: 99%
“…The average copper leaching degree was approximately 80 %. Sokić et al [7] performed acid leaching of copper from a copper oxide-sulphide ore excavated from the copper mine Cerovo, a part of the RTB Bor. These authors reported the leaching degree of copper of 73.8 % after 3 h in 0.3 M sulphuric acid solution.…”
Section: Introductionmentioning
confidence: 99%